2018
DOI: 10.1111/caje.12336
|View full text |Cite
|
Sign up to set email alerts
|

Big data analytics in economics: What have we learned so far, and where should we go from here?

Abstract: Research into predictive accuracy testing remains at the forefront of the forecasting field. One reason for this is that rankings of predictive accuracy across alternative models, which under misspecification are loss function dependent, are universally utilized to assess the usefulness of econometric models. A second reason, which corresponds to the objective of this paper, is that researchers are currently focusing considerable attention on so-called big data and on new (and old) tools that are available for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 124 publications
1
16
1
Order By: Relevance
“…Finally, we find that the use of real‐time data matters when forecasting interest rates using NS‐type models, in the sense that we overturn the findings of Swanson and Xiong (2018). In particular, using fully revised data, Swanson and Xiong find that big data such as that used in this paper “matter,” since variables other than yields enter into their MSFE‐best NS‐type models, even when forecast combinations are considered.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Finally, we find that the use of real‐time data matters when forecasting interest rates using NS‐type models, in the sense that we overturn the findings of Swanson and Xiong (2018). In particular, using fully revised data, Swanson and Xiong find that big data such as that used in this paper “matter,” since variables other than yields enter into their MSFE‐best NS‐type models, even when forecast combinations are considered.…”
Section: Introductionsupporting
confidence: 71%
“…When combination forecasts are included in our analysis, thus, there are no unspanned risks (i.e., risks not spanned by bond or bound returns), and all relevant forecasting information is contained in the term structure. In the context of our experiments, this indicates that the use of fully revised macroeconomic data may have an important confounding effect upon results obtained when forecasting yields, as prior empirical evidence suggests that diffusion indexes are often useful for predicting yields when constructed using fully revised data, regardless of whether forecast combination is used, or not (see Swanson & Xiong, 2018). This suggests that one possible explanation for our finding concerning the usefulness of macroeconomic diffusion indexes pre Great Recession has to do with model misspecification, particularly since our MSFE‐best combination utilizes all of our purely yield driven models.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Hansen, Memahon, & Prat (2017) Saltzman & Yung (2018) showed that business and economic related uncertainty is related to future weakness in output, higher unemployment, and term premium by using natural language processing techniques. Swanson & Xiong (2018) indicated that big data are useful when predicting the term structure of interest rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…series of subsequent corrections. Today, high frequency economic time series allow researchers to produce and adjust their forecasts far more frequently (Baldacci et al, 2016;Bok, Caratelli, Giannone, Sbordone, & Tambalotti, 2018;Einav & Levin, 2014a, 2014bSwanson & Xiong, 2018), even in real-time (Croushore, 2011). Not only are today's time series updated more frequently, but there are more of them available than ever before (Bok et al, 2018) on a much more heterogeneous set of topics (Einav & Levin, 2014b), often with near population-level coverage (Einav & Levin, 2014a).…”
mentioning
confidence: 99%